ANALISIS DETERMINAN TINGKAT KEDALAMAN KEMISKINAN DI KECAMATAN KARANGASEM KABUPATEN KARANGASEM BALI - Dewa Ayu Indah Puspita Dewi; Made Kembar Sri Budhi (widya balina, 2025)
Abstract. Poverty depth is a measure of the average gap in expenditure of each poor person to the poverty line, by focusing on the expenditure of the poor as a benchmark in determining the level of poverty in an area.This study aims to analyze the simultaneous and partial influence of social capital, education level, and employment status on the level of poverty depth in Karangasem District. This study was conducted in Karangasem District with a sample size of 100 respondents using a non-probability sampling method and data collection methods, namely observation, structured interviews, and in-depth interviews. The data analysis technique used was multiple linear regression analysis. The results of the study showed that social capital, education level, and employment status simultaneously had a significant effect on the level of poverty depth in Karangasem District. Partially, social capital and education level had a negative and significant effect, while employment status partially had a positive and significant effect on the level of poverty depth in Karangasem District. Employment status had a dominant effect on the level of poverty depth in Karangasem District.